Natural vegetation strips (NVS) and Gmelina cropping systems - Mamicpic, M.A.E.; Tinsley, R.L.; Magcale-Macandog, D. (Australian National University, 1998)
Recent rising demand for timber in Northern Mindanao, Philippines has driven smallholder farmers to plant fast-growing timber species, mostly Gmelina arborea, within their farms. The trees are commonly planted in portions of farms as block planting, along farm boundaries, or established along contour strips. Both natural vegetation strips (NVS) and tree cropping systems are examined here from biophysical and economic perspectives. In this paper, farmer surveys are reported with the aim of determining how livestock are raised in relation to the agricutural and tree components in both NVS and Gmelina block planting systems. The contribution of the animals to the productivity of each cropping system is established. Following the survey, the computer model, Soil Changes Under Agroforestry, is used to predict crop and tree yields for a number of years. These yields, in combination with the economic data collected, are input to a benefit-cost analysis that determines the long-term economic productivity of the cropping systems, with and without the animal component. The integration of livestock within both cropping systems was found to enhance economic productivity. The Gmelina system was the more profitable of the two systems but required a greater investment.